Srovnatelnost testových verzí slovenské maturitní zkoušky z anglického jazyka - Hulešová, Martina (Cizí jazyky a jejich didaktiky: teorie, empirie, praxe, 2021)
Title in English: Test versions equivalence of the Slovak upper-secondary school leaving examination The research presented in this book strives to answer how test versions equivalence - a necessary condition for meaningful and fair interpretation and comparison of students' results - could be achieved in the context of high-stakes examination. The research was carried on the Slovak upper-secondary school leaving examination in English at B1 level, namely on the tests of receptive skills operationalized between 2012 and 2015. Theoretical research on the methods and procedures and the application of some of them on the Slovak examinations in the empirical part provided deep insight into the degree of comparability of the test versions used between 2012 and 2015 and made it possible to identify problem areas in terms of test versions comparability. The research helped to identify suitable methods and approaches that might enable to develop equivalent test versions and subsequently, to interpret meaningfully the test results and the measured construct, i.e. students' language proficiency.